Potential for Biofuels for Transport in Developing Countries - Kojima, Masami; Johnson, Todd (World Bank, Washington, DC, 2014)
This note is based on a longer report published by ESMAP in 2005. The report responds to the increasing number of requests from developing countries to help assess the commercial viability of biofuels for transport in the next 5 to 10 years. This brief draws from the successful Brazil experience and illustrates socioeconomic considerations for establishing biofuel programs in developing countries.